Impulsivity Is Related to Prescription Opioid Misuse in People With Chronic Pain Through Pain Catastrophizing and Emotional Distress. - Esteve-Zarazaga, Rosa; Ramírez-Maestre, María del Carmen; Serrano-Ibáñez, Elena Rocío; López-Martínez, Alicia Eva (Wiley, 2025)
Abstract Background: This study investigated the role of impulsivity as a personality variable predisposing to prescription opioid misuse. Pain catastrophizing, as well as anxiety, depression, and pain intensity, were postulated as potential serial mediators in this relationship. Methods: The sample comprised 366 individuals with chronic pain. We conducted correlational and serial mediation analyses to investigate the relationships between the study variables. Results: The results showed that pain catastrophizing partially mediated the relationship between impulsivity and prescription opioid misuse. Depression and anxiety also partially mediated the relationship between pain catastrophizing and prescription opioid misuse, although pain intensity did not mediate this relationship. Impulsivity was also indirectly associated with prescription opioid misuse through pain catastrophizing, anxiety, and depression. Conclusions: Our findings highlight the key role of impulsivity in prescription opioid misuse and contribute to understanding its mechanisms of action. Based on these results, clinical interventions could target emotion-related impulsivity and cognitive control deficits to reduce rumination. Future research could investigate the relationships identified in this study using the specific dimensions of impulsivity.
Keywords: Ansiedad; Depresión mental; Opiáceos - Abuso; anxiety; depression; impulsivity; pain catastrophizing; prescription opioid misuse